Mathematical models from transdisciplinarity: Complexity and Reality (Agroindustria, Sociedad y Ambiente, 2019)
Mathematical models, as they have been known since ancient times, show a formal domain, where logic and objectivity define their cognitive spine. However, postmodernity has generated a paradigmatic revolution based on transdisciplinarity and complexity, which oriented towards a systemic vision, demonstrate the inability of current mathematics, to explain processes or phenomena from an interconnected, related, changing reality more practice and less idealistic. This essay aims to analyze mathematical models based on transdisciplinarity, complexity and systemic reality, Ontology, Epistemology and Gnoseology highlighting the need for a conceptual transformation in established models that allow applicability to real situations and phenomena. The critical analysis of several metatheors allows us to support the reevaluation of mathematical models, to the new paradigmatic demands; which requires more than quantifying, determining the interrelations, complementarities and semantic connections that face reality, from the most complex systems.
Keywords: Mathematical models; transdisciplinarity; complexity; systems theory; education